Strategi Penyusunan Pesan Informatif – Persuasif Dalam Data Covid-19 Oleh Humas Diskominfo Kota Bogor di Media Sosial - Shafa Tsamara Nugraini; Abdul Kholik (Universitas Gadjah Mada, 2021)
This research aims to find out the strategy of message preparaon conducted by Diskominfo Bogor City in managing COVID-19 data through social media. The preparaon of the message is done so that the message that wants to be conveyed can be understood and there is no mispercepon to the people of Bogor City. Public relaons government takes a role in managing data, with the strategy of composing messages before publicaon can minimize things - unwanted things happen. The research approach used is qualitave and the method used is descripve method. In this study there is a theory according to Cassandra cited by Hafied Cangara, namely the preparaon of informave messages and the preparaon of persuasive messages. This informave message management strategy and persuasive management technique are carried out by the Bogor City Communicaon and Informaon Office to build public understanding of informaon or news published through social media..The conclusion is diskominfo Bogor city conducts several strategies of draing messages that are informave and persuasive to manage COVID-19 data uploaded to social media. However, there are sll weaknesses in the COVID-19 data that makes people sll unable to read the contents of messages from COVID-19 data uploaded through social media Diskominfo Bogor City.